Change sings eaudiobook A children's anthem. - Gorman, Amanda (Listening Library, 2021)
A lyrical audiobook from presidential inaugural poet Amanda Gorman and #1 New York Times bestselling illustrator Loren Long   "I can hear change humming In its loudest, proudest song. I don't fear change coming, And so I sing along."   In this stirring, much-anticipated audiobook by presidential inaugural poet and activist Amanda Gorman, anything is possible when our voices join together. As a young girl leads a cast of characters on a musical journey, they learn that they have the power to make changes—big or small—in the world, in their communities, and in most importantly, in themselves.    With lyrical text, Change Sings is a triumphant call to action for everyone to use their abilities to make a difference.